EFFECT OF SEASONS ON PHYSIOLOGICAL AND HEMATOLOGICAL VALUES IN PUNGANUR CATTLE - B.R. NAIK; A.V.N.SIVA KUMAR; A.RAVI, K.V.BRAMHAIAH; V.PRAVEEN CHAKRAVARTHI (International Journal of Pharma and Bio Sciences, 2013)
The present study was conducted to establish base line physiological and hematology values in Punganur cattle in different age groups (bulls, cows, young bulls, heifers, and male and female calves) and during different seasons (monsoon, winter and summer). The mean rectal temperature (oF), respiration, pulse and heart rate (per min.) were significantly higher (P<0.01) in young animals than in adult cows and bulls and also during summer than during monsoon and winter seasons. The mean RBC and WBC counts differed significantly (P<0.01) among the age groups and were higher during summer than either during monsoon or winter seasons. The Hemoglobin content was not significantly different among the age groups but was significantly higher (P<0.01) during summer than during either monsoon or winter seasons. The mean PCV (%) in different age groups and also during monsoon, winter, and summer seasons were not significantly different. The mean ESR (mm/hr) in different age groups was not significantly different but was significantly (P<0.01) higher during summer than during winter. The DLC count (%) among different age groups of Punganur cattle was significantly different (P<0.01) for Neutrophils, Eosinophis, Basophils, Lymphocyte except for monocytes. Neutrophils and lymphocytes were significantly higher (P<0.01) during summer, Eosinophils and Basophils during monsoon while Monocytes count was significantly higher (P<0.01) during winter than during other seasons.